(untitled) (Research Journal, 2024)
This study aims to identify the social relations and livelihood experiences of widowed women in Nepali society. A narrative research design has been adopted for this study, and participants have been selected through the purposive selection method. The area of this study is Phakphokthum Rural Municipality Ward No. 1 of Ilam District. Feminist theory has been used as the theoretical framework of this study, based on which the results have been analyzed. In-depth interviews, observation forms, and memo-writing tools have been used for data collection. After transcribing the procedurally collected data, three levels of coding were developed to construct themes. Based on the themes thus constructed, the data is analyzed. Finding in two sentences the widowed women of Nepal are living a discriminatory life with economic, social, and psychological crises.